Valuation And Quantification Of Assets, Liabilities, And Income In Pharmaceutical Company In Indonesia (Journal of Pharmaceutical Negative Results, 2023)
This study aims to analyze the valuation and quantification of assets, liabilities and income in pharmaceutical companies in Indonesia. This research is qualitative in nature, namely research that holistically intends to understand the phenomenon of what is the subject of research, be it events, perceptions, or actions, and in a descriptive way the approach used uses a conceptual approach, and literature studies The results of the study show that valuation and asset quantification use three approaches, namely the market data comparison approach, the revenue capitalization approach and the cost approach, where pharmaceutical companies in Indonesia tend to use these three approaches in assessing assets, then the debt policy of pharmaceutical companies in Indonesia when viewed from the the debt to equity ratio shows a fluctuating value where the risk of debt is still high for the company due to the high value of this ratio, furthermore the income of pharmaceutical companies in Indonesia tends to fluctuate where during the covid 19 pandemic pharmaceutical companies experienced significant revenue growth.